A Novel Technique for Secure Data Retrieval - Sugunan, Sarika; Azeez, Arifa (IJRDO -Journal of Computer Science Engineering, 2015)
Mobile nodes in a hostile network are likely to sufferfrom intermittent network connectivity and frequent partitions.Disruption-tolerant network (DTN) technologies are becominga productive solution that allow wireless devices tocommunicate with each other and access the confidentialinformation or command reliably by exploiting external storagenodes. The most critical issues in this scenario are theenforcement of authorization policies and the policies updatefor secure data retrieval in wireless networks. Ciphertextpolicyattribute-based encryption (CP-ABE) is a promisingcryptographic solution to the access management problems.However, the problem of applying CP-ABE in decentralizedDTNs introduces several security and privacy challenges withregard to the attribute revocation, key escrow, and coordinationof attributes issued from different authorities. In this work, wepropose a secure data retrieval scheme using CP-AUBE fordecentralized DTNs where multiple key authorities managetheir multiple attributes independently. Also we enforce a grouporiented attribute based encryption and also incorporate anefficient attribute and key renewal technology. The grouporiented encryption is done with concept of Bucketizationwhich produces an optimal solution. Hence the proposedmechanism demonstrates how to securely and efficientlymanage the confidential data distributed in the disruptiontolerantnetwork